Opportunities from the COVID-19 Pandemic: Being Greener through Online and E-Learning Methods - Chalil, Diana; Barus, Riantri (Journal of Sustainability Perspectives, 2021)
To implement physical distancing during the COVID-19 pandemic, many universities around the world have applied online and E-learning methods. Although faced with several obstacles, online and E-learning methods also provide many opportunities. One of them include the reduction of paper usage, which in 2019 totaled to 394 million tons worldwide. To analyze such an opportunity, this study was conducted at Universitas Sumatera Utara (USU) by involving 232 students and 113 lecturers from 16 faculties. Data were obtained using a structured online questionnaire. The results show that paper usage at USU can be reduced through online and e-learning methods by 48,008,800 sheets per year or equivalent with approximately 4,003 trees. This amount is totalled from lecturer research activities, lecture materials, and student final projects, which are 240,000, 44,800,000 and 3,000,000 sheets, respectively. To realize this, USU is required to improve internet facilities and e-learning access, train lecturers and students to use and manage said facilities, and train lecturers to prepare materials specifically designed for online and e-learning.